Utilization of Sustainable Palm Empty Fruit Bunch Sorbents for Carbon dioxide Capture - N. S., Nasri; U. D., Hamza; A., Abdulkadir; Siti Noraishah, Ismail; M. M., Hamed (2013)
Sustainable porous carbons have been produced via pyrolysis of palm empty fruit bunch (EFB) and then modified using hydrogen reduction and treatment with phenol for increase in hydrophilic character. The sorbents were tested for CO2 capture. The EFB based sorbent materials were characterized for morphology and chemical functional groups. Characterization of the porous carbons covered four samples: hydrogen reduced, hydrophilic treated, bio oil impregnated and CO2 uptake samples. FTIR analysis showed presence of hydroxyl, carbonyl, aliphatic, esters, alcohol, phenol and analysis showed presence of hydroxyl, carbonyl, aliphatic, esters, alcohol, phenol and carboxylic groups on the surfaces of the sorbent materials. Absence of C=O in thehydrophilic treated samples could be traced back to reaction of the phenol and compounds containing carbonyl groups. Absence of C-O stretching for ethers in the carbon captured samples could be related to oxidation of ethers in CO2.Spectra at 557.5cm-1 could be due to adsorption of CO2 bending stretch.